2014
DOI: 10.1016/j.nbd.2014.05.015
|View full text |Cite
|
Sign up to set email alerts
|

DLK-dependent signaling is important for somal but not axonal degeneration of retinal ganglion cells following axonal injury

Abstract: Injury to retinal ganglion cell (RGC) axons triggers rapid activation of Jun N-terminal kinase (JNK) signaling, a major prodeath pathway in injured RGCs. Of the multiple kinases that can activate JNK, dual leucine kinase (Dlk) is known to regulate both apoptosis and Wallerian degeneration triggered by axonal insult. Here we tested the importance of Dlk in regulating somal and axonal degeneration of RGCs following axonal injury. Removal of DLK from the developing optic cup did not grossly affect developmental R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
118
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(129 citation statements)
references
References 48 publications
(113 reference statements)
9
118
1
1
Order By: Relevance
“…Thus, different aspects of RGC decline may occur at different rates or be regulated by distinct mechanisms. Consistent with this, deficiency in the dual leucine kinase (Dlk) signaling pathway alters somal but not axonal RGC degeneration (Fernandes et al, 2014). In contrast to our findings, significant reductions in beta tubulin III labeled RGCs were observed in a transient ocular hypertension model of glaucoma in Cx3cr1 gfp/gfp C57Bl6/J mice (Wang et al, 2014).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Thus, different aspects of RGC decline may occur at different rates or be regulated by distinct mechanisms. Consistent with this, deficiency in the dual leucine kinase (Dlk) signaling pathway alters somal but not axonal RGC degeneration (Fernandes et al, 2014). In contrast to our findings, significant reductions in beta tubulin III labeled RGCs were observed in a transient ocular hypertension model of glaucoma in Cx3cr1 gfp/gfp C57Bl6/J mice (Wang et al, 2014).…”
Section: Discussionmentioning
confidence: 85%
“…This is also the case for diverse neurodegenerative ocular diseases, including glaucoma (Karlstetter et al, 2015). In glaucoma, retinal ganglion cells (RGCs) progressively degenerate, with the different neuronal compartments (soma, axon, dendrites, and synapses) declining at different times and potentially by different mechanisms (Libby et al, 2005a; Whitmore et al, 2005; Conforti et al, 2007; Howell et al, 2007; Calkins, 2012; Fernandes et al, 2014). In addition, multiple studies in human and experimental glaucoma suggest a link between the progressive deterioration of RGCs and alterations of glial cell types (Yuan and Neufeld, 2001; Naskar et al, 2002; Neufeld and Liu, 2003; Nakazawa et al, 2006; Inman and Horner, 2007; Bosco et al, 2011, 2015b; Lye-Barthel et al, 2013; Chong and Martin, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Deletion of DLK expression in an optic nerve crush model provided significant RGC survival (Welsbie et al, 2013), and reduced expression of stress response, inflammatory and apoptotic genes, like ATF3, CHOP and Bim , but had little effect on regenerative properties of the axon after injury (Watkins et al, 2013). It was recently shown that Dlk -deficiency delayed somal RGC death after optic nerve injury, but axonal degeneration was unaffected (Fernandes et al, 2014). Downstream targets for DLK include MKK4/7 and JNK activation, the latter of which can participate in a feedback loop and stabilize DLK activity (Huntwork-Rodriguez et al, 2013).…”
Section: The Role Of Bax In Mouse Retinal Ganglion Cell Pathophysimentioning
confidence: 99%
“…There is some disagreement regarding the role of DLK1 in RGCs. Axon degeneration was not delayed after optic nerve crush in DLK1-deficient mice (Fernandes et al, 2014). While this suggests that kinases other than DLK1 may be capable of JNK activation for axon degeneration, a separate study showed that phosphorylation of c-Jun, a target of JNK, was dependent on DLK1 after optic nerve crush (Watkins et al, 2013).…”
Section: Energy In Axonsmentioning
confidence: 99%
“…DLK-1, after trophic deprivation, is JNK dependent and contributes to both axon degeneration and cell body apoptosis (Ghosh et al, 2011). Interestingly, DLK1 knockout in a optic nerve crush model did not protect RGC axon structure or function as measured by CAP amplitude (Fernandes et al, 2014), suggesting that degeneration in these axons is governed differently than those in development (Hoopfer et al, 2006) and potentially other sensory systems (Miller et al, 2009). Others determined that deficiency in DLK1 protected RGC somas from apoptosis and proximal axons from degeneration after optic nerve crush (Watkins et al, 2013).…”
Section: Energy In Axonsmentioning
confidence: 99%